Efeito de Lactobacillus rhamnosus e de Lactococcus lactis isolados de queijo de coalho na viabilidade e produção de enterotoxina B por staphylococcus aureus FRI-S6 em queijo - Bianca Seridan de Assis (2010)
Homemade cheese, which consumption is widely known through the world, is frequently attached to food borne intoxication break outs. The most prevalent pathogen in these cases is Staphylococcus aureus, responsible for the majority of cases of mammary infection in cows and transported by food manipulation. At the present study, S. aureus was inoculated in sterile lab produced cheese among to Lactobacillus rhamnosus and Lactococcus lactis, in real concentrations, as found in home made cheese. Analysing enumeration values, the ALB did not have the power of reduce S. aureus counts, but showed evidences of enterotoxin B production inhibition capacity. This power was strongest for L. lactis.